IDENTIFICATION OF PHYTO CONSTITUENTS PRESENT IN MEDICINAL PLANT - Saba Hadi; Baan M. Twaij (European Journal of Agricultural and Rural Education, 2022)
The active ingredients in medicinal plants contain complex compounds that are produced or stored in various plant organs and tissues. In addition to economic and export value, these compounds are of high pharmaceutical, nutritional and health value and have formed the formulation and basis of many drugs. Many methods have been proposed for their separation, including chromatography, spectrometry and electrophoresis, which we have fully described in this article.